Major and minor U small nuclear RNAs genes characterization in a neotropical fish genome: Chromosomal remodeling and repeat units dispersion in Parodontidae - Azambuja, Matheus (2022)
In association with many proteins, small nuclear RNAs (snRNAs) organize the spliceosomes that play a significant role in processing precursor mRNAs during gene expression. According to snRNAs genic arrangements, two kinds of spliceosomes (major and minor) can be organized into eukaryotic cells. Although in situ localization of U1 and U2 snDNAs have been performed in fish karyotypes, studies with genomic characterization and functionality of U snRNAs integrated into chromosomal changes on Teleostei are still scarce. This study aimed to achieve a genomic characterization of the U snRNAs genes in Apareiodon sp. (2n = 54, ZZ/ZW), apply these data to recognize functional/defective copies, and map chromosomal changes involving snDNAs in Parodontidae species karyotype diversification. Nine snRNA multigene families (U1, U2, U4, U5, U6, U11, U12, U4atac and U6atac) arranged in putatively functional copies in the genome were analyzed. Proximal Sequence Elements (PSE) and TATA-box promoters occurrence, besides an entire transcribed region and conserved secondary structures, qualify them for spliceosome activity. In addition, several defective copies or pseudogenes were identified for the snRNAs that make up the major spliceosome. In situ localization of snDNAs in five species of Parodontidae demonstrated that U1, U2, and U4 snDNAs were involved in chromosomal location changes or units dispersion. The U snRNAs defective/pseudogenes units dispersion could be favored by the probable occurrence of active retrotransposition enzymes in the Apareiodon genome. The U2 and U4 snDNAs sites were involved in independent events in the differentiation of sex chromosomes among Parodontidae lineages. The study characterized U snRNA genes that compose major and minor spliceosomes in the Apareiodon sp. genome and proposes that their defective copies trigger chromosome differentiation and diversification events in Parodontidae.